Environmentally Sustainable Economic Growth - Stelian Brad; Bogdan Mocan; Emilia Brad; Mircea Fulea (Amfiteatru Economic Journal, 2016)
Economic growth and sustainable development are important issues for social prosperity. Sustainable development strives for moderate and responsible use within the economic activity of the limited resources of our planet, whereas economic growth does not limit the resource exploitation and energy, being mainly focused on productivity increase. From this perspective, both conceptual and operational contradictions occur between the two pillars of prosperity. This paper looks to these contradictions and proposes some streams of intervention such as economic growth and environmental sustainability to operate in harmony. A structured framework for innovative problem solving is considered in this respect. Results of this research show that it is possible to induce smart measures in the economic system for directing businesses towards new paradigms where economic growth is possible without negative effects on environmental sustainability.
Keywords: O47; Q01; 330; economic competitiveness; economic growth; sustainable development; innovation policy; prosperity